Birth order and paediatric allergic disease: A nationwide longitudinal survey. Issue 5 (27th February 2018) - Kikkawa, T.; Yorifuji, T.; Fujii, Y.; Yashiro, M.; Okada, A.; Ikeda, M.; Doi, H.; Tsukahara, H.
Summary: Background: Environmental factors seem to be related to the incidence of allergic disease. Children with a later birth order are often exposed to environments, where pathogens and endotoxins can be found, and thus have a higher risk of developing infectious diseases. Therefore, birth order is regarded as an indicator that reflects post‐natal environment. However, longitudinal studies are limited on this subject. This study sought to elucidate the relationships between birth order and allergic disease. Methods: From a nationwide longitudinal study that followed children born in 2001 (n = 47 015), we selected doctors' visits for 3 types of allergic disease—bronchial asthma, food allergy and atopic dermatitis—from infancy to 12 years of age and conducted binomial log‐linear regression analysis to evaluate the associations between birth order and these diseases. We adjusted for the child and parental factors and estimated risk ratio (RR) and 95% confidence interval (CI) for each outcome. Results: The associations between birth order and bronchial asthma were diverse; later birth order increased the risk in early childhood, but decreased the risks during school age. For example, the adjusted RR comparing third‐born or higher and first‐born children was 1.19 (95% CI, 1.05‐1.35) between 30 and 42 months of age, but was 0.76 (95% CI, 0.65‐0.89) between 10 and 11 years. Later birth order was generally protective for food allergy but increased the risk of atopic dermatitis. Conclusion: The influence of birth order depended on the type of allergic disease and the childhood period. Childhood is unique in terms of physical and immunological development, and the immune response to the post‐natal environment in childhood appears to be heterogeneous.